Maggot Optimization as Organic Waste Bioconversion in Sembubuk Village, Muaro Jambi Regency - Ade Adriadi; Rizky Desryan Syah; M. Khafid Rizaldi; Muhammad Fernando; Nur Umi Hasanah; Arel Del Kita Putra; Angely Ignatia Silalahi; Shinta Khana Afriya; Elisa Tri Erawati; Suci Rahmadhani; Rizky Fariz Diouf; Pandu Tulus Pambudi; Bela Apriani Br. Panjaitan; Ahmad Abdan Solikhin; Yuliniar Senjaya; M. Saiful Muarif (Jurusan Ilmu Sosial dan Ilmu Politik, 2026)
Sembubuk Village has great potential in the agricultural and livestock sectors, yet it faces challenges in sub-optimal organic waste management. This study aims to implement the MAGGOTIN innovation as an integrated solution through waste bioconversion technology using Black Soldier Fly (BSF) larvae. The methods included regional potential identification, community knowledge surveys, technical cultivation training, and the construction of